The Effects of Scheduled Visitation on the Physiological Indices of Conscious Patients Admitted at intensive Care Units - Hojat Rezaie; Tabandeh Sadeghi; Fatemeh Abdoli (Mashhad University of Medical Sciences, 2015)
Background: Visitation of patients admitted at intensive care units (ICUs) is a controversial issue in the field of health care. It is commonly believed that the presence of family members might bring about physiological changes, such as tachycardia and hypertension, in ICU patients. Aim: This study aimed to evaluate the effects of scheduled visitation on the physiological indices of conscious patients at the ICU. Method: This experimental study was conducted on 90 conscious patients admitted at the ICU of Ganjavian Hospital in Dezful, Iran in 2014. Patients were randomly divided into two groups of intervention and control. In the control group, patient visits were carried out in accordance with normal procedures of the ward. In the intervention group, patients were visited by relatives and family members for 30 minutes, preferably in evening shifts. Physiological indices of the patients were recorded before, during and after scheduled visitation. Data analysis was performed in SPSS V.18 using independent T-test and one-way ANOVA with repeated measures. Results: In this study, mean age of patients in the intervention and control groups was 42.1±19.1 and 39.4±19.6 years, respectively. In the intervention group, systolic blood pressure had a more significant reduction at 10 and 30 minutes after visitation compared to the control group (independent T-test, P0.05). Implications for Practice: According to the results of this study, scheduled visitation by family members caused no significant differences in the physiological indices of ICU patients. It is recommended that future studies be conducted as to confirm this finding and revise patient visitation policies in hospitals.